San Giuseppe di Nazareth secondo san Girolamo - Mirri, Luciana (Vox Patrum, 2025)
The present study concerns what profile emerges and what consideration Saint Jerome has for Saint Joseph of Nazareth. The analysis considers the Dalmatian Doctor’s works in which he is most cited, but does not omit other writings where he appears. In fact, in addition to the Against Elvidius (383), the Jewish Questions (389/391), the Commentary on Matthew (393), a Homily on the Nativity of the Lord (400/410), mentions are found in commentaries on prophets or Pauline letters and one in The Illustrious Men (393). Even these occasional texts are sometimes interesting for assessing the importance of constant attention over time and a confirmation of the author’s thinking on the subject. Four themes emerge from the Hieronymic writings: the philology of the name ‘Joseph’; Joseph’s genealogy; Joseph’s virginity; the holiness of the ‘just’ Joseph. Jerome’s texts are made to speak, interpreting his message. In addition to being the first Father of the Church to assert the virginity of Saint Joseph, he is in fact also the Author who holds him in esteem as a man trusted by the Most High and a privileged role as a witness of the Incarnation for the redemption of the world.